THE INFLUENCE OF STORE ENVIRONMENT, SALES PROMOTION AND PERCEIVED VALUE ON PURCHASE DECISION - CHAPHIRAY CHAPHIRAY; IRMA SATYA INDRIYANTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The purpose of this research is to test and analyze influence of Store Environment, Sales Promotion, and Perceived Value to Purchase Decision to Customer Ramayana in East Jakarta. The research design used in descriptive research and causality research. The sampling in the study used 206 respondent with purposivesampling. The research data is processed with IBM Statistic 22.0 as a tool. This study uses multiple regression analysis. The result showed that Store Environment, Perceived Value influence Purchase Decision, but for Sales Promotion not influence to Purchase Decision. Overall, independent variables affect Loyalty simultaneously.